Education and Economic Development in the Selected European Union Countries - Dudzevičiūtė, Gitana; Šimelytė, Agnė (European Journal of Sustainable Development, 2018)
This paper has aimed to investigate the education – economic development nexus in the selected European Union (EU) countries during the period of 1997 – 2016. Descriptive statistics analysis and econometric techniques have been applied for this purpose. Research results have revealed statistically significant interrelationships between education and economic growth in majority of the selected countries. However, only Belgium, France, Ireland and United Kingdom have demonstrated causal relationships between the variables under consideration. In these countries the unidirectional causality running from education to economic development has shown that increase in the share of population having tertiary education promotes economic performance. In the remaining countries neither increasing share of tertiary education effects on economic development nor growing real GDP promotes tertiary education of the population. The insights of the research could be useful in achieving the goals for Europe 2020, where tertiary education is highlighted as one of the five measurable targets. Keywords: education, economic development, Granger causality, European Union.